Investigation of transient photocurrent response of triple pn junction structure. Issue 4 (1st February 2013) - Schidl, S.; Polzer, A.; Dong, J.; Schneider‐Hornstein, K.; Zimmermann, H.
Abstract : The transient photocurrent response of a vertically stacked triple pn junction structure, which can detect three different colours simultaneously, is investigated. The triple pn junction structure is designed based on the effect that the penetration depth in silicon depends on light wavelength. To increase the bandwidth of optical sensor systems the transient photocurrent response is a critical parameter. The transient response is measured by applying three different light wavelengths to this triple junction structure. This triple pn junction structure is fabricated in a 0.6 µm BiCMOS technology using a p − p + epitaxial wafer without any process modification. Based on the measurement results, it can be concluded that this triple pn junction structure can be applied to optical sensors without optical filters and the total data rate of this structure can reach up to 100 Mbit/s.